(Table 2) Uranium and some major element contents in deep sea clayey sediments of the Pacific Ocean - Gleb N Baturin (PANGAEA, 2002)
Uranium and phosphorus were investigated in 107 samples of deep-sea clayey sediments of the Northern- and Central Pacific Ocean, in which grain size composition, as well as contents of organic carbon, opaline silica, iron, and manganese were determined previously. Uranium content in these sediments varies from 0.5 to 3.2 ppm and that of phosphorus from 0.05 to 0.84%. Spatial distribution of uranium in sediments has a latitudinal character but does not coincide with distributions of phosphorus, organic carbon, and iron. Correlation of uranium contents with contents of these elements is also absent. Average contents of uranium in groups of sediments enriched in phosphorus, organic carbon, and iron are close to each other and vary from 1.6 to 2.3 ppm. Ratios of average contents of uranium to ones of these elements, as well as calculated percentages of uranium bound with various sediment components evidence that phosphate in deep-sea clays plays only minor role as uranium carrier, whereas predominant part of this element is bound with iron, organic matter, and presumably clay minerals.
Supplement to: Baturin, GN (2002): Uranium and phosphorus in deep-sea clays of the Pacific Ocean. Translated from Okeanologiya, 2002, 42(5), 757-764, Oceanology, 42(5), 723-730